PENGEMBANGAN MODUL E-LEARNING BERBASIS WEB DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN PADA MAHASISWA IKIP BUDI UTOMO MALANG - Abadi Abadi (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2018)
Research on the development of e-learning module in learning Pendidikan Pancasila dan Kewarganegaraan has a goal where the e-learning module into an alternative web-based teaching materials that are easily accessible and used IKIP Budi Utomo Malang students. The e-learning module is web-based learning Pendidikan Pancasila dan Kewarganegaraan intended for students IKIP Budi Utomo Malang where subjects Pendidikan Pancasila dan Kewarganegaraan be compulsory subject as the formation of characters berbudiutama college students who are in harmony with the vision of campus IKIP Budi Utomo Malang that is "Became Higher Education university Education and Training excellence of superior, healthy and standard international in the year 2022 "where Berbudiutama in the vision as an effort to form a noble personality or berakhlaq noble (akhlaqul karimah). IKIP Budi Utomo Malang must carry and realize the values of usefulness, awareness, compliance, propriety and Indonesian. Implementation of research begins with Research and information, where Research and information is used to collect information about the needs of learning materials that are easily accessible by students with the sophistication of IT. Then proceed to the ADDIE model. The result of research of the development of web-based e-learning module in learning Pendidikan Pancasila dan Kewarganegaraan to improve the character of good students of IKIP Budi Utomo Malang.